2021
DOI: 10.7150/jca.61379
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics Mediated by DRP1 and MFN2 Contributes to Cisplatin Chemoresistance in Human Ovarian Cancer SKOV3 cells

Abstract: Cisplatin (DDP) is the first-line chemotherapeutic agent for ovarian cancer. However, the development of DDP resistance seriously influences the chemotherapeutic effect and prognosis of ovarian cancer. It was reported that DDP can directly impinge on the mitochondria and activate the intrinsic apoptotic pathway. Herein, the role of mitochondrial dynamics in DDP chemoresistance in human ovarian cancer SKOV3 cells was investigated. In DDP-resistant SKOV3/DDP cells, mitochondrial fission protein DRP1 was down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 67 publications
2
15
1
Order By: Relevance
“…In SKOV3 cisplatin-resistant cells, the mitochondrial fission protein DRP1 is down-regulated, while the mitochondrial fusion protein MFN2 is up-regulated. In accordance with the expression of DRP1 and MFN2, the average mitochondrial length was significantly increased in these cells, supporting again that mitochondrial dynamics contribute to the development of cisplatin resistance in ovarian cancer cells [ 122 ]. This was also shown by the silencing of DRP1 or overexpression of MFN2 that promote the resistance of SVOK3 cells to cisplatin [ 122 ].…”
Section: Mitochondrial Dynamics In Ovarian Cancersupporting
confidence: 55%
See 1 more Smart Citation
“…In SKOV3 cisplatin-resistant cells, the mitochondrial fission protein DRP1 is down-regulated, while the mitochondrial fusion protein MFN2 is up-regulated. In accordance with the expression of DRP1 and MFN2, the average mitochondrial length was significantly increased in these cells, supporting again that mitochondrial dynamics contribute to the development of cisplatin resistance in ovarian cancer cells [ 122 ]. This was also shown by the silencing of DRP1 or overexpression of MFN2 that promote the resistance of SVOK3 cells to cisplatin [ 122 ].…”
Section: Mitochondrial Dynamics In Ovarian Cancersupporting
confidence: 55%
“…In accordance with the expression of DRP1 and MFN2, the average mitochondrial length was significantly increased in these cells, supporting again that mitochondrial dynamics contribute to the development of cisplatin resistance in ovarian cancer cells [ 122 ]. This was also shown by the silencing of DRP1 or overexpression of MFN2 that promote the resistance of SVOK3 cells to cisplatin [ 122 ]. In addition, the pro-fission activity of DRP1, as mentioned before, depends on its phosphorylation status.…”
Section: Mitochondrial Dynamics In Ovarian Cancersupporting
confidence: 55%
“…Previous studies have suggested that mitochondrial dynamics could influence chemotherapy sensitivity in cancer cells. In our previous studies, it was found that mitochondrial dynamics participate in cisplatin resistance in ovarian cancer, and the level of mitochondrial fusion was higher in cisplatin resistant ovarian cancer cells ( 43 ). However, the contrary results were obtained in GC cells, as increased mitochondrial fission was observed in SGC-7901/DDP cells compared with that in SGC-7901 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cells and cell culture. The human EOC SK-OV-3 cell line, which is commonly used in the study of cisplatin-resistant in serous EOC (29,30), was purchased from Jiangsu KeyGEN BioTECH Co., Ltd. The human EOC cisplatin-resistant SK-OV-3/DDP cell line was purchased from Shanghai Chuan Qiu Biotechnology Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%